2004
DOI: 10.1111/j.1542-474x.2004.94568.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Stage of Left Ventricular Diastolic Dysfunction with P Wave Dispersion and Occurrence of Atrial Fibrillation after First Acute Anterior Myocardial Infarction

Abstract: P maximum and P dispersion are increased, and AF occurrence risk is higher in patients with pseudonormal/restrictive filling pattern after first anterior AMI. The stage of diastolic dysfunction is an independent predictor of P wave measurements and AF occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…Gunduz et al [16], studied the effect of diastolic dysfunction on Pd and did not find a significant relation between Pd and stage of diastolic dysfunction. Yilmaz et al [17], however, found independent relationship between stage of diastolic dysfunction and Pd in patients after first anterior myocardial infaction. In our study patients with severe OSA did show impaired diastolic function with lower E/A ratio and Pd was found to be correlated with E/A ratio.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Gunduz et al [16], studied the effect of diastolic dysfunction on Pd and did not find a significant relation between Pd and stage of diastolic dysfunction. Yilmaz et al [17], however, found independent relationship between stage of diastolic dysfunction and Pd in patients after first anterior myocardial infaction. In our study patients with severe OSA did show impaired diastolic function with lower E/A ratio and Pd was found to be correlated with E/A ratio.…”
Section: Discussionmentioning
confidence: 96%
“…We manually calculated P-wave measurements by magnifying lens instead of computer-assisted P-wave calculations. However, our method has been used in previous studies [17,18]. Our study group included patients without a history of AF, therefore the clinical significance of Pd was not evaluated in this study.…”
Section: Limitationsmentioning
confidence: 97%
“…89 Numerous other investigations have described the association of myocardial infarction and AF. [90][91][92] Not all evidence, however, suggests an independent association of diastolic dysfunction and AF in general. A study in elderly patients aged ≥65 years from the Olmsted County, MN, showed abnormal diastolic relaxation to be predictive of AF only in those with an enlarged LA (≥27 mL/m 2 ).…”
Section: Diastolic Dysfunctionmentioning
confidence: 99%
“…Another study conducted by Yilmaz et al 14 showed maximum P wave duration and P wave dispersion are increased, and atrial fibrillation occurrence risk is higher in patients with pseudonormal/restrictive filling pattern after first acute anterior myocacardial infarction. The grade of diastolic dysfunction is an independent predictor of P wave measurements and AF occurrence.…”
Section: Discussionmentioning
confidence: 99%